Unmaking waste in production and consumption : towards the circular economy - Crocker, Robert, 1952-; Saint, Christopher, active 2018; Chen, Guanyi; Tong, Yindong (Emerald Publishing Limited, 2018)
The legacies of a century of fossil-fuel based development and overconsumption, of treating the environment as a waste sink for industry and agriculture, have left devastating impacts on the earths air, water and land, and these are directly implicated in Climate Change. In response, a number of global institutions and nations, including the European Union and China, have committed themselves to the development of a circular economy. This will require a transformation of todays linear economy of make, use and dispose as the market dictates, into a Circular Economy.The aim of the Circular Economy is to decouple economic growth from resource and energy use through iterative, systemic social, economic and technological reform. This book presents new theoretical and practical insights into this concept, based on case studies from both the developing and developed world, with an emphasis on economic and material transformation, design for reuse and waste reduction, industrial symbiosis(the planned circulation of resources and energy within an industrial setting),and social innovation and entrepreneurship. Four central themes emerge through the essays presented here: theimportance of restorative design in transforming resource flows through both production and consumption, the value of understanding and enumerating wastes in more detail to enable their reuse, the central role of advancing technology and applied science to further this transformation of materials for reuse, and finally, a reconfiguration of design, consumption and retail, so that the present linear economy of make, use and trash can be replaced with a more circular model.